if = 3abc and a,b,c are positive numbers, then
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a 3 + b 3 + c 3 = 3abc
a 3 + b 3 + c 3 - 3abc = 0.
(a + b + c )( a 2 + b 2 + c 2 -ab - ac -bc) = 0
here (a + b + c) cannot be equal to zero since a,b,c are positive. Therefore ( a² +b² +c²-ab - ac -bc) = 0.
2a² + 2b² + 2c² -2ab - 2ac - 2bc = 0.
a² + b² -2ab + a² +b² +2c² - 2ac -2bc = 0.
(a-b)² + a² + c² -2ac + b² + c² -2bc = 0.
(a-b)² + (a-c)² + (b-c)² = 0
(a-b)² , (a-c)² ,(b-c)² >=0
since postive numbers cannot be added to make zero, each bracket should be zero a-b = 0 a-c = 0 b-c =0 a = b a= c b = c a = b = c